A Note on the Redistributive Effect of Immigration - Rob Euwals; Hans Roodenburg (Institute for the Study of Labor (IZA), 2003)
In this paper, we study gains and losses that accrue to natives because of immigration. The gain on the aggregated level is called the ?immigration surplus?, which can be seen as analogous to a consumer surplus. We derive changes in the earnings of native owners of production factors by employing a stylized model with capital and two types of labour. We claim that the changes in earnings are larger than reported by previous studies, and we propose a new method to tally them up to the immigration surplus.
Keywords: J31; D60; D30; J61; 330; immigration; wages; economic welfare; redistribution; Einwanderung; Verteilungswirkung; Produktionsfunktion; Lohn; Wohlfahrtseffekt; Theorie